SoTL in the Commons: Elephant, Authenticity and Journey - Ora Kwo (International Journal for the Scholarship of Teaching and Learning, 2007)
Excerpt: I find it useful to refer to the metaphor of an international feel of the ‘elephant’ presented by Pat Hutchings in the inaugural issue of this journal. Indeed, definitions of scholarship of teaching and learning can be very different depending on which parts of the anatomy one is feeling (or seeing, or experiencing). With a specific focus on the role of theory, Pat took readers through variations of how theory is perceived in different traditions to reach a common ground for all: theory is not an end in itself, but a condition for doing better what we most care about as educators as essential to a meaning-making, knowledge-building process.